Minimization of torque ripple and flux droop using optimal DTC switching and sector rotation strategy - Ahmad Tarusan, Siti Azura (2022)
Direct Torque Control (DTC) is a well-known AC control scheme for its robustness and simplicity. Although DTC provides excellent dynamic torque control performance, but it has several drawbacks. The digital implementation of the hysteresis band controller, which causes a delay action, may result in huge ripple and switching frequency inconsistency for DTC torque performance. Since the torque slope is already disturbed in the hysteresis bandwidth in various operating conditions, the limiting voltage vector of the two-level inverter in the conventional DTC limits the control switching frequency in the hysteresis controller. Another drawback of conventional DTC is that the presence of voltage drop in a stator resistance at low operating speeds causes a droop in stator flux performance. This problem occurs as the voltage vectors deviate from the usual state, where it manifests itself as a change in the boundary sector of the circular flux locus. Therefore, an optimal DTC switching strategy and an optimal DTC sector rotation strategy to overcome the problems in a three-phase induction motor have been proposed. A five-level cascaded H-bridge (CHB) inverter was used in the optimal DTC switching strategy because it had many voltage vectors and could be used for a variety of speed operations. Its objectives were to propose the optimal switching vector in minimizing torque ripple and controlling switching frequency at the steady-state of various speed operations. A modification torque error status and a look-up table of a five-level CHB inverter were used to implement the specified optimal voltage vectors. Another objective was to formulate and evaluate the optimal DTC sector rotation strategy that can reduce stator flux droop in the variation of torque and speed in steady-state and dynamic response. The optimal sector rotation strategy is determined using an analytical model of shifted angle that incorporates speed and torque variables which is dynamically tuned. Both proposed strategies were compared with conventional method and verified through simulation and experimentation works. MATLAB/Simulink software is used to simulate the proposed strategies while a complete setup system consists of a DS1104 digital signal processor (DSP)-board (to implement the DTC algorithm), Field-programmable Gate Arrays (FPGA) (to implement the blanking circuit), two-level and five-level (CHB) inverter circuit, gate driver circuit, and a 1.1 kW induction motor with 2 kW DC generator as a load is developed for testing and verification purpose. A compromise between simulation and experimentation works resulted in significant improvements; 1) a reduction of torque ripple up to 50% and a reduction of switching frequency up to 40%, 2) an ability to maintain a similar magnitude of stator flux by eliminating the droops. In conclusion, the method introduced demonstrates the effectiveness of DTC performance which maintains its simple structure as well as offers ease in modification for a desired control purpose.